Baseline sputum eosinophil+neutrophil subgroups’ clinical characteristics and longitudinal trajectories for NHLBI Severe Asthma Research Program (SARP 3) Cohort - Hastie, A.T. (J Allergy Clin Immunol, 2020)
Combined elevated sputum eosinophils+neutrophils in asthma associated with lowest lung function, greater healthcare utilization, and longitudinally, further spirometric loss, implicating cell-cell interactions or overlapping inflammatory pathways while increased eosinophils or neutrophils alone show less effect.